Effect of substrate temperature on microstructures and dielectric properties of compositionally graded BST thin films - 张柏顺 郭涛 章天金 王今朝 全祖赐 (Transactions of Nonferrous Metals Society of China, 2006)
Compositionally graded Ba1-xSrxTiO3 （BST） （x = 0-0.3） thin films were prepared on Pt/Ti/SiO2/Si substrate at different substrate temperatures ranging from 550 ℃ to 650 ℃ by radio-frequency （rf） magnetron sputtering. The effect of substrate temperature on the preferential orientation, microstructures and dielectric properties of compositionally graded BST thin films was investigated by X-ray diffraction, scanning electron microscopy and dielectric frequency spectra, respectively. As the temperature increases, the preferential orientation evolves in the order： randomly orientation→ （111） → highly oriented （111） （α（111）= 60.2%）. The surface roughness of the graded BST thin films varies with the substrate temperatures. No visible internal interface in the compositionally graded thin films can be observed in the cross-sectional SEM images. The graded BST thin films deposited at 650 ℃ possess the highest dielectric constant and dielectric loss, which are 408 and 0.013, respectively.